Occurrence of multiple infections of rodents with parasites and bacteria in the Sibang Arboretum, Libreville, Gabon - Patrice Makouloutou-Nzassi; Chimène Nze-Nkogue; Boris Kevin Makanga; Neil Michel Longo-Pendy; Judi Armel Bourobou Bourobou; Branly Cordia Bikie Bi Nso; Etienne François Akomo-Okoue; Cherone-Cheba Mbazoghe-Engo; Félicien Bangueboussa; Silas Lendzele Sevidzem; Ghislain Wilfried Ebang Ella; Lillian B. Mangama Koumba; et al. (Veterinary World)
Background and Aim: Rodents are carriers or reservoirs of various bacteria, protozoa, viruses, and ectoparasites. Given the proximity of various rodent species and humans, there is a potential for the transmission of pathogens. Data on ecto- and endo-parasite prevalence in rodent populations in Gabon are limited. To fill this gap, we conducted a study in Libreville to investigate the occurrence of ecto- and endo-parasites in rodents.